Search for charged higgs bosons decaying into top and bottom quarks in pp̄ collisions - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (American Physical Society (APS), 2009)
We describe a search for production of a charged Higgs boson, qq̄′→H+, reconstructed in the tb̄ final state in the mass range 180≤MH+≤300GeV. The search was undertaken at the Fermilab Tevatron collider with a center-of-mass energy s=1.96TeV and uses 0.9fb-1 of data collected with the D0 detector. We find no evidence for charged Higgs boson production and set upper limits on the production cross section in the types I, II, and III two-Higgs-doublet models (2HDMs). An excluded region in the (MH+, tanβ) plane for type I 2HDM is presented. © 2009 The American Physical Society.